2010
DOI: 10.1200/jco.2010.31.1670
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutation Is Frequently Associated With CTNNB1 Mutation or MYCN Amplification and Is Compatible With Long-Term Survival in Medulloblastoma

Abstract: The contradictory results in the recent literature concerning the prognostic value of TP53 mutation might be explained by different frequencies of WNT MBs, different frequencies of patients with Li-Fraumeni syndrome, and different cumulative doses of alkylating drugs applied in these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 35 publications
9
72
0
3
Order By: Relevance
“…In addition, although somatic Trp53 mutations are found most frequently in WNT-MB, they have little prognostic significance in this subgroup. Therefore, subgroup identity remains the major predictor of prognosis for WNT-MB (16).…”
Section: Medulloblastomamentioning
confidence: 99%
“…In addition, although somatic Trp53 mutations are found most frequently in WNT-MB, they have little prognostic significance in this subgroup. Therefore, subgroup identity remains the major predictor of prognosis for WNT-MB (16).…”
Section: Medulloblastomamentioning
confidence: 99%
“…Of note, many mouse models of MB, including these MYC-driven group 3 models, require the loss of Trp53 function; yet somatic mutations of TP53 occur mostly in WNT and SHH medulloblastoma and are associated with MYCN rather than MYC amplification (Pfaff et al 2010;Rausch et al 2012). The absence of these mutations in group 3 tumors means that TP53 loss is not required for human tumor initiation, that another cooperative genetic event assists tumor initiation, or that the TP53 pathway is in some other way compromised.…”
Section: Myc In the Group 3 Subgroupmentioning
confidence: 99%
“…97 Examination of p53 gene status in 310 primary human MB tumors representing all 4 MB subgroups confirmed that p53 gene mutations in MB are rare and failed to correlate with chromosome 17p deletions. 96 In addition, this study yielded several novel insights. First, p53 gene mutations are overrepresented in MB tumors that have a mutation in the CTNNB1 gene (encoding β-catenin), indicative of Wnt activation, or that have a high level of NMYC amplification.…”
Section: Monographsmentioning
confidence: 83%
“…It has since been found that loss of 17p in MB and p53 status is unrelated. 88,96 New support for a role for p53 in MB tumorigenesis comes from a greater understanding of heterogeneity underlying MB tumors. Through the integration of molecular and clinical markers, including genetic abnormalities, patient age at time of diagnosis, tumor histology, and overall and progression-free survival, 4 MB subgroups with distinct signaling pathway alterations and clinicopathological features have been identified (see Table 1).…”
Section: Monographsmentioning
confidence: 99%